2001
DOI: 10.1128/jb.183.14.4374-4381.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that an Additional Mutation Is Required To Tolerate Insertional Inactivation of theStreptomyces lividans recAGene

Abstract: In contrast to recA of other bacteria, the recA gene of Streptomyces lividans has been described as indispensable for viability (G. Muth, D. Frese, A. Kleber, and W. Wohlleben, Mol. Gen. Genet. 255:420-428, 1997.). Therefore, a closer analysis of this gene was performed to detect possible unique features distinguishing the Streptomyces RecA protein from the well-characterized Escherichia coli RecA protein. The S. lividans recA gene restored UV resistance and recombination activity of an E. coli recA mutant. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…To our knowledge, the only other recA gene for which a disruption was achieved only under special circumstances is that of Streptomyces lividans (Muth et al, 1997), in which viable mutant strains were found to lack only short extensions of the RecA C-terminus, and displayed residual RecA activity. Recent studies in S. lividans suggested that an additional mutation (resulting in a sporulation defect) is required to tolerate total recA deficency, although its role remains obscure (Vierling et al, 2001). Although the observed inability to inactivate recA2 demands further investigation, our present data indicate that this locus might be required for sustaining cell viability in B. megaterium.…”
Section: Expression Of Reca1 and Reca2 Is Damageinduciblementioning
confidence: 60%
“…To our knowledge, the only other recA gene for which a disruption was achieved only under special circumstances is that of Streptomyces lividans (Muth et al, 1997), in which viable mutant strains were found to lack only short extensions of the RecA C-terminus, and displayed residual RecA activity. Recent studies in S. lividans suggested that an additional mutation (resulting in a sporulation defect) is required to tolerate total recA deficency, although its role remains obscure (Vierling et al, 2001). Although the observed inability to inactivate recA2 demands further investigation, our present data indicate that this locus might be required for sustaining cell viability in B. megaterium.…”
Section: Expression Of Reca1 and Reca2 Is Damageinduciblementioning
confidence: 60%
“…In fact, ϳ10% of E. coli recA mutants are anucleate, and an additional fraction show signs of chromosomal degradation (35,49). By contrast, Streptomyces lividans recA mutants are not viable at all unless additional compensatory mutations are selected that suppress the lethal effect of the absence of RecA (41). In T. thermophilus recA mutants, there are also defects in chromosome condensation and asymmetric partitioning, but this could represent only a minor fraction (ϳ10 to 15%) of the cells and cannot by itself explain the dramatic decrease in viability observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of a rare compensatory mutation enabling the spirochete to overcome recA inactivation as a necessary precondition for isolation of a recA null mutant cannot be ruled out. Such a compensatory mutation has been suggested for tolerance of a recA null mutation in Streptomyces lividans (57).…”
Section: Discussionmentioning
confidence: 99%